Sufi Motives in the Literature of the Egyptian Period - Aripova, Zukhra (International Journal of Psychosocial Rehabilitation, 2020)
There are some historical relations between Uzbekistan and Egypt. The period governed by mamluks covers 1250-1517 years. This period includes 2 governing periods of bakhriys (1250-1382) and burjiys (1382- 1517). After the occupation of Bagdad, the center of Islamic and abbasiykhalifas in 1258 by moguls, the sultan of mamluks Zahir Baybars changed the capital to Kahira. Regarding this period, many educated people, hadith learners and sufiis began to come to Egypt and started to learn the knowledge of tasavvuf in Kahira. In this research the knowledge of tasavvuf and the books of sufiis which were written in the period of mamluks were learned. Sufiis gained the respect of sultans and other statesmen. Sufism influenced many spheres of Muslim world, including philosophy, poetry, behavior and politics. He achieved huge governance over the public and directed his power against salibs and moguls. During the period of mamluks a great deal of religious works was kept by ulamas, hadith learners and faqikhs (fiqh learners). Majority of the scholars had lots of books in astronomy, language, literature and religion.